Relationships between changes in the state of neuroendocrine regulation and immunity in patients of Truskavets’ spa - Popovych, Andriy; Popovych, Igor; Popovych, Dariya; Ruzhylo, Sofiya; Żukow, Xawery (Journal of Education, Health and Sport, 2021)
Background. Earlier we showed that the balneotherapeutic complex of Truskavets’ spa have significant modulating effects on parameters of EEG&HRV and Immunity of patients with chronic pyelonephritis and cholecystitis in remission accompanied of neuroendocrine-immune complex dysfunction. Were detected the close relationships between EEG, HRV, endocrine and immune parameters as well as between changes in EEG&HRV and immune parameters under the influence of balneotherapy. The aim of this study was to analyze the relationships between changes in the state of neuroendocrine regulation and immunity of the same patients. Materials and Methods. The object of clinical-physiological observation were 22 men aged 23-70 years, who underwent rehabilitation treatment of chronic pyelonephritis and cholecystitis in remission in the Truskavets’ spa. The examination was performed twice, before and after a 9-11-day course of balneotherapy. The subject of the study were the parameters of the electroencephalogram, heart rate variability, hormones and immunity. Results. The method of canonical correlation analysis states that the changes in immunity caused by balneotherapy are determined by the constellation of alaptation hormones by 98,9%, the autonomic nervous system by 99,9%, the central nervous system by 99,7%. Conclusion. Immunomodulatory effect of balneotherapy is realized through the neuro-endocrine mechanism.